Isolated calcaneal tuberculous osteomyelitis in a 13-year female: a diagnostic dilemma: rare case report and review of literature - Chaudhari, Kunal; Shah, Nadir Z.; Pawar, Eknath D.; Marfatia, Ankit (International Journal of Research in Orthopaedics, 2023)
Foot and ankle involvement in osteoarticular tuberculosis is uncommon and isolated calcaneal tubercular osteomyelitis of foot bones sparing nearby joints with an osteolytic defect is even more rare. Worsening of the disease can occur over a time involving nearby joints and small bones if diagnostic and therapeutic phase are delayed. We present a retrospective study of osteolytic variety of foot calcaneal bone tuberculosis. We present a case report of 13-year female with isolated osteolytic variety of calcaneal tuberculous osteomyelitis to highlight the clinical, radiological features and management challenges of the condition. Biopsy was done to confirm tissue diagnosis based on Gene Xpert, AFB staining, MGIT culture, and histopathology. Surgical intervention was done in form of debridement and sinus tract removal as a diagnostic and therapeutic purpose to prevent further involvement of a nearby joints and small bone with cystic destruction. Isolated calcaneal tubercular osteomyelitis cases are still found to be seen in our environment though considered a rare. When tuberculous pathology is limited to the isolated calcaneal bone sparing the other joints, the prognosis is better than in osteoarticular disease, as there is less deformity, and hence, less residual pain and disability.